Derivation of research diagnostic criteria for insomnia: report of an American Academy of Sleep Medicine Work Group. - Edinger, J; Bonnet, M; Bootzin, R; Doghramji, K; Dorsey, C; Espie, C; Jamieson, A; McCall, W; Morin, C; Stepanski, E (2004)
Insomnia is a highly prevalent, often debilitating, and economically burdensome form of sleep disturbance caused by various situational, medical, emotional, environmental and behavioral factors. Although several consensually-derived nosologies have described numerous insomnia phenotypes, research concerning these phenotypes has been greatly hampered by a lack of widely accepted operational research diagnostic criteria (RDC) for their definition. The lack of RDC has, in turn, led to inconsistent research findings for most phenotypes largely due to the variable definitions used for their ascertainment. Given this problem, the American Academy of Sleep Medicine (AASM) commissioned a Work Group (WG) to review the literature and identify those insomnia phenotypes that appear most valid and tenable. In addition, this WG was asked to derive standardized RDC for these phenotypes and recommend assessment procedures for their ascertainment. This report outlines the WG's findings, the insomnia RDC derived, and research assessment procedures the WG recommends for identifying study participants who meet these RDC.